Tatalaksana Maloklusi Skeletal Kelas 2 Disertai Riwayat Kebiasaan Buruk Menghisap Ibu Jari Menggunakan Oral Screen Dan Alat Orthodonti Cekat - Yossy Eko Arimbi; Iwan Ahmad M. (Riviera Publishing, 2025)
Skeletal Class II malocclusion is a condition involving disharmony between the maxilla and mandible, often caused by a combination of genetic and environmental factors, including deleterious habits such as thumb sucking. This habit may exacerbate anterior dental proclination, mandibular retrusion, and occlusal disturbances. This case management involves a combined approach of habit-breaking therapy using an oral screen and fixed orthodontic treatment to correct dental position and jaw relationship. The case report demonstrates successful control of the thumb-sucking habit through behavioral management and the use of an oral screen, followed by the application of fixed orthodontic appliances to correct the malocclusion. Treatment outcomes included improved facial esthetics, occlusal function, and behavioral modification. Comprehensive and multidisciplinary management is essential to achieve optimal results in patients with skeletal discrepancies and persistent oral habits.